Legal and ethical implications of wastewater monitoring of SARS-CoV-2 for COVID-19 surveillance - Gable, Lance (J Law Biosci, 2020)
Scientists have observed that molecular markers for COVID-19 can be detected in wastewater of infected communities both during an outbreak and, in some cases, before the first case is confirmed. The Centers for Disease Control and Prevention and other government entities are considering whether to add community surveillance through wastewater monitoring to assist in tracking disease prevalence and guiding public health responses to the COVID-19 pandemic. This scientific breakthrough may lead to many useful potential applications for tracking disease, intensifying testing, initiating social distancing or quarantines, and even lifting restrictions once a cessation of infection is detected and confirmed. Yet, new technologies developed in response to a public health crisis may raise difficult legal and ethical questions about how such technologies may impact both the public health and civil liberties of the population. This paper describes recent scientific evidence regarding COVID-19 detection in wastewater, identifying public health benefits that may result from this breakthrough, as well as the limitations of existing data. The paper then assesses the legal and ethical implications of implementing policy based on positive sewage signals. It concludes that the first step to implementing legal and ethical wastewater monitoring is to develop scientific understanding. Even if reliability and efficacy are established, limits on sample and data collection, use, and sharing must also be considered to prevent undermining privacy and autonomy in order to implement these public health strategies consistent with legal and ethical considerations.